Are Women of Reproductive Age Aware of Gynecological Cancers? - Aysun Perim Ketenciler; Meryem Metinoğlu; Sevda Karakaş; Gülin Göncü (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Objective: This descriptive study aimed to determine the awareness levels of women of reproductive age regarding gynecological cancers. Materials and Methods: The study was conducted with 379 women aged between 15 and 49 registered at two separate Family Health Centers in Tekirdağ city center between May 2022 and April 2023. Data were collected using the "Gynecological Cancers Awareness Scale" and an "Introductory Information Form." Descriptive statistics including number, minimum, maximum, percentage, mean, and standard deviation were provided using the SPSS 21 package program. Shapiro-Wilk normality test, Independent Sample T-test, One Way ANOVA, Pearson correlation test, and Bonferroni test were used for data analysis. A statistical significance level of p <0.05 was accepted. Results: The mean age of the women in the study was 34 ±11 years, with 61.5% being married. The average Gynecological Cancers Awareness Scale (GCAS) score was 157.1 ±17.1 (range 106-205). Sub-dimension scores were: "Early Diagnosis and Information Awareness" 17.1 ±2.3 (range 10-20), "Risk Awareness" 28.4 ±5.3 (range 13-45), "Prevention Awareness" 22.4 ±3.4 (range 12-30), and "Routine Checks and Serious Illness Perception" 89.0 ±11.9 (range 45-110). In the study, 48.5% of the women knew about early diagnosis methods for gynecological cancers, and 76% were aware of the Cancer Early Diagnosis Screening and Education Center (KETEM). Women who were aware of risky health behaviors and cancer symptoms had higher awareness levels (p <0.05). There was no significant difference between the number of pregnancies and births and awareness levels (p >0.05). Conclusion: The result shows that women have a moderate level of awareness about gynecological cancers; however, their knowledge of gynecological cancer symptoms and awareness of risky health behaviors is higher. Additionally, more than half of the participants (60.7%) have never had a gynecological examination.